Oracle of Lost Causes : John Newman Edwards and His Never-Ending Civil War - Hulbert, Matthew C. (Book collections on Project MUSE., 2023)
"John Newman Edwards was a soldier, a father, a husband, and a noted author. He was also a virulent alcoholic, a duelist, a culture warrior, and a man perpetually at war with the modernizing world around him. From the sectional crisis of his boyhood and the battlefields of the western borderlands to the final days of the Second Mexican Empire and then back to a United States profoundly changed by the Civil War, Oracle of Lost Causes chronicles Edwards's lifelong quest to preserve a mythical version of the Old World-replete with aristocrats, knights, damsels, and slaves-in North America. This odyssey through nineteenth-century American politics and culture involved the likes of guerrilla chieftains William Clarke Quantrill and "Bloody Bill" Anderson, notorious outlaws Frank and Jesse James, Confederate general Joseph Orville Shelby, and even Emperor Maximilian I and Empress Charlotte of Mexico. It is the story of a man who experienced Confederate defeat not once but twice, and how he sought to shape and weaponize the memory of those grievous losses. Historian Matthew Hulbert ultimately reveals how the Civil War determined not only the future of the vast West but also the extent to which the conflict was part of a broader, international sequence of sociopolitical uprisings."--